2017
DOI: 10.4102/sajce.v7i1.437
|View full text |Cite
|
Sign up to set email alerts
|

The influence of executive function challenges on the behavioural adaptation of one learner with autism spectrum disorder

Abstract: <p><span>In South Africa, many learners with autism spectrum disorder (ASD) attend mainstream and private schools. This study explores the influence of executive function (EF) challenges experienced by one learner with ASD on his behavioural adaptation in an inclusive school environment. An interpretive case study approach was followed to help understand one unique ASD learner and explain the complexity of the behavioural adaptation challenges that he was experiencing. Observations and an interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Five studies on IE of pupils with ASD ( De Jager, 2011 ; De Jager & Condy, 2017 ; Majoko, 2016 , 2017 , 2018 , 2019 ) reported barriers to their inclusion that were not discussed for other disorders, specifically challenging sensory experiences and rigidity of thought, interests and routines. For example, in one study, the majority of teachers recognised that: ‘ Children with ASD have complication transitioning from one academic or social activity or environment to another ’ ( Majoko, 2016 ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies on IE of pupils with ASD ( De Jager, 2011 ; De Jager & Condy, 2017 ; Majoko, 2016 , 2017 , 2018 , 2019 ) reported barriers to their inclusion that were not discussed for other disorders, specifically challenging sensory experiences and rigidity of thought, interests and routines. For example, in one study, the majority of teachers recognised that: ‘ Children with ASD have complication transitioning from one academic or social activity or environment to another ’ ( Majoko, 2016 ) …”
Section: Resultsmentioning
confidence: 99%
“…(Mohamed & Laher, 2012) 'He cannot pay attention in class or finish his work'. (Engelbrecht et al, 2003) Pupils with DD themselves reported struggling with their attention and learning: 'When teacher is talking it is difficult to listen and understand so I look in the window' (pupil with DD; Okyere et al, 2019a) Five studies on IE of pupils with ASD (De Jager, 2011;De Jager & Condy, 2017;Majoko, 2016Majoko, , 2017Majoko, , 2018Majoko, , 2019 reported barriers to their inclusion that were not discussed for other disorders, specifically challenging sensory experiences and rigidity of thought, interests and routines. For example, in one study, the majority of teachers recognised that:…”
Section: Context For Inclusionmentioning
confidence: 99%